Self realisation : its meaning and method - "Krishnananda, Swami" (Tehri-Garhwal, 1999)
The contents of this book form the subject of five lectures addressed to seekers in the Ashram of The Divine Life Society, some years back, and it is hoped that these suggestions will do some good to many a searching spirit.
Keywords: Profectionaism